Linguistic Attitudes From Quechua-Speaking Natives Towards Aymara Speakers - Ochoa Yupanqui, Adán (2020)
The main purpose of this study is to show the attitudes from Quechua native speakers towards Aymara native speakers. This survey is cualitative, its sample is non-probabilistic, and it is composed by five people Quechua native speakers who live in Lima and arrived to this city since they were young. Two of them were born in two localities of Puno, other two people come from localities of Cusco and the remaining one comes from Apurimac. Their ages are from 52 to 76 years old. The data collection was made by a semi structured interview composed by direct and indirect questions to find out their linguistic attitudes towards the aymara language and their users in several aspects. In this article I conclude that Quechua speakers tend to show linguistic attitudes which vary among neutral and negative ones regarding to the cognitive component, because of job opportunities and the prestige of Aymara language at the national level.